EFFICACY OF NEEM SEED EXTRACT±ASHWAGANDHA FOR THE TREATMENT OF ENDOMETRITIS IN BUFFALOES - KADAM, P D; MARKANDEYA, N M; KUMAWAT, B L; SAWALE, A G; LAWANGE, S R; ANBHULE, R S (The Indian Journal of Animal Reproduction, 2022)
test of cervico-vaginal mucus (CVM) and endometrial cytology were divided equally into three groups. Group-I containing fresh endometritic buffaloes (repeated ≤7 times) was administered once with Methanolic Neem seed extract (100 mcg/ml) @ 30 ml by intrauterine (IU) route, Group-II consisting of chronic endometritic buffaloes (repeated >7 times) was administered with Methanolic Neem seed extract (100 mcg/ml) @ 30 ml IU once only plus 15 gm Ashwagandha powder by oral route for 5 days and Group-III as a control group was administered with placebo as 30 ml PBS through IU. In both treated groups, pH of CVM deceased (p<0.05) after treatment and white side test turned negative in all recovered buffaloes. Polymorphonuclear cell count was reduced (p<0.05) posttreatment in recovered cases. Immunoglobulin level in serum of chronic endometritic buffaloes increased (p<0.05) post-treatment. A higher recovery rate was observed in Group-II as 75% against 66.7% in Group-I and nil recovery in control group. Pregnancy rates were recorded as 62.5%, 55.5% and nil in group-I, II and III, respectively.